2021
DOI: 10.1080/1057610x.2020.1866737
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Radical Right Groups’ Movements across Social Media Platforms – A Case Study of Changes to Britain First’s Visual Strategy in Its Removal from Facebook to Gab

Abstract: Her research expertise lies at the intersection of Digital Discourse Analysis and Criminology. Relevant funded projects she leads include examining radical right groups' use of social media, profiling online sexual groomers' language use and exploring constructions of trust in crypto-drug markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Stating that "[w]e do not do this lightly, but they have repeatedly posted content designed to incite animosity and hatred against minority groups, which disqualifies the Pages from our service" [29]. Whilst a fringe political organisation, the group had a large social media presence, with more than 1.8 million followers and 2 million likes on its Facebook page, more than double the amount of the Labour party (the mainstream party with the most likes) [49,61]. The following year Facebook went further designating the group and its leaders under its new definition of 'dangerous groups and individuals', along with a number of other far-right organisations and individuals [89].…”
Section: Terrorism As a Driver For Deplatforming: From Isis To Political Extremistsmentioning
confidence: 99%
“…Stating that "[w]e do not do this lightly, but they have repeatedly posted content designed to incite animosity and hatred against minority groups, which disqualifies the Pages from our service" [29]. Whilst a fringe political organisation, the group had a large social media presence, with more than 1.8 million followers and 2 million likes on its Facebook page, more than double the amount of the Labour party (the mainstream party with the most likes) [49,61]. The following year Facebook went further designating the group and its leaders under its new definition of 'dangerous groups and individuals', along with a number of other far-right organisations and individuals [89].…”
Section: Terrorism As a Driver For Deplatforming: From Isis To Political Extremistsmentioning
confidence: 99%
“…The opaque process that underlies rule development and enforcement introduces unknown and potentially systematic variation to analyses of social media data. Social media platforms are essentially exempt from legal liability for the content posted by their users in both Europe and the United States (Nouri, Lorenzo-Dus and Watkin 2019, 4–5), and platform policy statements like ‘Each situation is evaluated on a case by case basis and ultimately decided upon by a cross-functional team, [and is influenced by] the changing nature of online speech, including how our rules are applied and interpreted in different cultural and social contexts’ (Twitter: Our approach to policy development and enforcement philosophy) indicate large-scale variation among and within platforms. As such, patterns not only differ from country to country, as rules are enforced differently depending on cultural and social contexts, but also over time as social media platforms are free to change the rules and procedures that guide their rule enforcement.…”
mentioning
confidence: 99%
“…Additionally, organisations are working to circumvent content removal strategies as seen in the sharing of news sources example. As already argued, unless there is some standardization in platform responses across the ecosystem, it is going to be difficult to break the whack-a-mole pattern that has emerged over recent years (Nouri, Lorenzo-Dus, Watkin, 2021).…”
Section: Twittermentioning
confidence: 99%
“…The findings of this literature review revealed a small number of studies examining terrorist use of small file-sharing sites and alternative platforms. Similar to Urman and Katz (2020) Telegram research, a study by Nouri et al (2021) examined the issue of whack-a-mole in the far-right. This research examined UK far-right group Britain First as they were removed from Facebook and migrated to Gab which is an alternative platform known for attracting far-right groups and individuals because of its lack of willingness to regulate and remove content.…”
Section: Small File-sharing Sites and Alternative Platformsmentioning
confidence: 99%
See 1 more Smart Citation